Penyuluhan Dampak Pernikahan Dini Dan Kesehatan Reproduksi Bagi Anak Remaja Di Kabupaten Mojokerto - Hikmah Muhaimin; Dhiyan Septa Wiharan; Dian Wijaya; Mohammad Resi Abdul Basith (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2022)
The impact of early marriage and reproductive health for adolescents is very influential on all factors, both economic, social, health and educational factors. And early marriage seems to still be happening, including in Indonesia. Especially in Mojokerto Regency, the numbers are very fantastic, the people still do this. Usually the causes of early marriage are cultural and socio-economic factors. Some parents still have the notion that children can be a "savior" of family finances when they get married. There are also those who consider unmarried children to be an economic burden on the family. Actually, the bride who is still in her teens is the most disadvantaged party in early marriage. Because this event will sacrifice the physical and mental development of women. Getting pregnant at a young age and dropping out of school will limit women's career opportunities. In addition, early marriage can increase the risk of domestic violence. Community service activities were held at the P2KBP2 Office Hall, Mojokerto Regency, Jln RA. Basuni No. 19 Sooko Mojokerto. The purpose of this activity is to find out what are the factors behind early marriage and reproductive health for adolescents and what impact this has on the household and the social, economic, educational and health environment of couples who marry early. Partners for community service activities are IIDI Mojokerto Branch and Puspa Majapahit, Mojokerto Regency. The participants of the activity are OSIS representatives for high school students or the equivalent in Mojokerto Regency. The methods in this community service are lectures, discussions, and questions and answers. The result of this drawing is the existence of counseling ambassadors representing 1 youth mass organization or 1 student council member in each high school or equivalent to be able to conduct counseling or socialization in every secondary school in each of these schools or the equivalent in all Mojokerto district.